The crime of disturbing food security - Tali Sultan Al-Shuwaili , Researcher. Eida; Hanoun Khalaf Al Darraji, Prof.Dr. Ghazi (Basra studies journal, 2025)
Food security is one of the most important areas that the legislator has tried to protect criminally, as the concept of food security is no longer limited to people obtaining the necessary food commodity, but also includes that these commodities are fit for human consumption, and free of all pollutants, whether chemical, radioactive, or genetically modified materials that harm human health and safety. The process of liberalizing international trade and Iraq’s openness to global financial markets has contributed to the ease of transferring money and production elements and the difficulty of investigating their perpetrators, all of which have contributed to the occurrence of food crises. The crime affecting food security is no longer a personal act are limited in effects to a narrow circle, but has become an aggression against the interests of society and affects the stability of countries from a social and political perspective. The role of criminal law is no longer an ordinary role, but has become more concerned with and attached to the main interests of society in light of contemporary criminal policy, which is the effective tool in protecting these interests by curbing the motives of criminal behavior that harms the interests of society, by preventing acts that undermine food security, such as acts of fraud and deception in goods or price manipulation, as well as acts that affect the health of the consumer and other acts that the legislator has criminalized with punitive texts, whether in the Penal Code or special laws, since criminal protection is superior to private interest.